A catalogue of land-based adaptation and mitigation solutions to tackle climate change - Maria Vincenza Chiriacò; Claudia Dămătîrcă; Sara Abd Alla; Sara Barilari; Rebeca Biancardi Aleu; Tommaso Brazzini; Tiago Capela Lourenço; Carlotta Annamaria de Carolis Villars; Suzie Durand; Giulio Di Lallo; Ricardo Encarnação Coelho; Océane Espin; et al. (Scientific Data)
Abstract Informing and engaging all actors in the land sector, including land-owners and managers, researchers, policy-makers and citizens, on the most effective sustainable land-based solutions and behavioural changes is a key strategy for achieving climate change adaptation and mitigation targets at the global as well as at EU and local level. One requisite to support actors in the land sector is to provide them publicly available, reliable and ready-to-use information related to the implementation of Land-based Adaptation and Mitigation Solutions (LAMS). Here we introduce a LAMS catalogue, a collection of meaningful quantitative and qualitative information on 60 solutions characterised according to a set of specifications (e.g., mitigation and adaptation potential, cost of implementation, suitability factors, synergies and trade-offs, drivers and barriers to the implementation). The catalogue offers a reliable, science-based tool useful for different users’ needs, including valuable references for deriving context-specific quantitative inputs to simulate and evaluate the performance of solutions over time using modelling tools, such as Integrated Assessment Models at any scale.